Moldovan media discourse on international legal mechanisms regulating mercenary participation in the Russian-Ukrainian War (2022-2024) - Igor Soroceanu (Clío, 2025)
This research explores the legal structures, military mobilization processes, and societal response mechanisms related to Moldovan citizens’ involvement in the Russian-Ukrainian conflict. The methodology includes case analysis of military engagement, review of judicial precedents on war crimes, and evaluation of state responses to disinformation campaigns. The findings highlight the International Legion for the Defense of Ukraine as a legitimate framework for foreign volunteers, distinct from mercenary activity. Empirical data indicate multi-generational military participation, standardized war crimes documentation, and institutional responses to information warfare. The study underscores the need for clear legal frameworks and institutional mechanisms to manage foreign military participation while safeguarding national security.